Mean Leeway space in Nepalese children attending a tertiary care hospital, Bhaktapur: A radiographic evaluation - Pradhan, Megha; Dhital, Shweta; Joshi, Ujjwal; Poudyal, Sijan (Journal of Kathmandu Medical College, 2020)
Background: Leeway space becomes important during the change of dentition and occlusal development. Objectives: The study was designed to measure the mean leeway space of maxilla and mandible of Nepalese children using Orthopantomogram radiographs and also to compare the difference between mean leeway space in male and female children. Methodology: After ethical approval, 270 OPG (Orthopantomogram) radiographs of age groups 6-12 years Nepalese children exhibiting mixed dentition were selected for the study after following the inclusion and exclusion criteria by convenience sampling method. A digital measurement in the OPG software was used to measure the mesiodistal width of deciduous canine and molars along with permanent canine and premolars in all quadrants. Results: The mean leeway space on maxilla was seen to be (0.86 ±1.97mm) while for mandible was (2.45± 1.85 mm).The leeway space in both maxilla and mandible was seen to be more in females (0.87 ± 1.87 mm) and (2.52 ± 1.85 mm) than in males (0.85 ± 2 mm) and (2.40 ± 1.90mm)respectively. Conclusion: The mean leeway space in Nepalese children was found to be less than the standard “Leeway space of Nance” which could be due to population tooth crown differences and various environmental factors. Further studies could be recommended in the future both radiographically and clinically for obtaining a standardized leeway space for Nepalese population.